2021
DOI: 10.17816/rcf194383-393
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory syndrome-2 (SARS-CoV-2): A solution of hydrogen peroxide and sodium bicarbonate as an expectorant for recanalization of the respiratory tract and blood oxygenation in respiratory obstruction (review)

Abstract: The immediate cause of death of patients in the final stage of a new coronavirus infection is hypoxia, which develops due to respiratory obstruction. In accordance with the standard of treatment of patients with the most severe atypical pneumonia with COVID-19, artificial lung ventilation and extrapulmonary blood oxygenation are used to preserve their lives. However, these methods do not eliminate airway obstruction, one of the causes of which is mucus hypersecretion. The review shows that a new vector for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…WAHPSs have been reported to consist of the following main ingredients: water, hydrogen peroxide and an alkali (preferably sodium bicarbonate) [20]. Many invented drugs have been shown to be able to dissolve thick masses of pus, blood clots, sulfur plugs, tear stones, mucus, sputum, meconium and other thick biological masses containing the enzyme catalase [23,24]. It has been established that WAHPSs, when locally interacting with sputum, mucus, pus, and serous fluid, are capable of exerting a pyolytic, mucolytic, and antihypoxic oxygen-releasing effect [25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…WAHPSs have been reported to consist of the following main ingredients: water, hydrogen peroxide and an alkali (preferably sodium bicarbonate) [20]. Many invented drugs have been shown to be able to dissolve thick masses of pus, blood clots, sulfur plugs, tear stones, mucus, sputum, meconium and other thick biological masses containing the enzyme catalase [23,24]. It has been established that WAHPSs, when locally interacting with sputum, mucus, pus, and serous fluid, are capable of exerting a pyolytic, mucolytic, and antihypoxic oxygen-releasing effect [25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…All the above solutions have a nonspecific local action provided by local hyperthermia, moderate alkalinity, osmotic activity, on the one hand, and the enzyme catalase contained in pus masses and other biological tissues, on the other hand. As a result of local application, all alkaline hydrogen peroxide solutions quickly turn these masses into a fluffy white oxygenated foam [22,23,25]. This has been shown to occur due to alkaline saponification of lipid and protein-lipid complexes and a cold boiling process caused by the formation of gas bubbles due to catalase splitting of hydrogen peroxide into oxygen gas and water and/or due to a decrease in the initial overpressure [33,34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, it has been reported that sputum, mucus, pus and other thick secretions may accumulate in the airways, especially in patients with bacterial or fungal superinfection [52][53][54][55][56][57]. In particular, it has been shown that serous fluid and pus can accumulate in the airways in tuberculosis, bronchiectatic disease, cystic fibrosis, purulent obstructive bronchitis, paragonimus, pulmonary strongyloidosis, legionary disease, and severe chest trauma [58][59][60][61][62]. Because asthma and COVID-19 can sometimes be combined with, not just bacterial and fungal superinfections, the airways of some patients may be filled not only with sputum and mucus, but also with thick pus [45,46,[63][64][65].…”
Section: Introductionmentioning
confidence: 99%